2019
DOI: 10.1093/pm/pnz071
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors in Painful Diabetic Neuropathy: A Systematic Review of Treatment Trials and Survey Studies

Abstract: Objective Diabetes mellitus is associated with a number of complications that can adversely impact patients’ quality of life. A common and often painful complication is painful diabetic neuropathy. The aims of this study were to systematically review and summarize evidence from studies of psychological treatments and psychosocial factors related to painful diabetic neuropathy and assess the methodological quality of these studies. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 72 publications
0
24
0
5
Order By: Relevance
“…DPN is a leading cause of worldwide disability [ 15 ], and it affects the quality of life due to chronic pain, high risk of falls [ 17 ], foot ulceration [ 18 ], and limb amputation [ 19 ]. Furthermore, DPN symptoms often lead to sleep disorders, anxiety, and depression [ 20 , 21 ]. The poor glycemic control causing hyperglycemia and microangiopathy is the common underlying pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…DPN is a leading cause of worldwide disability [ 15 ], and it affects the quality of life due to chronic pain, high risk of falls [ 17 ], foot ulceration [ 18 ], and limb amputation [ 19 ]. Furthermore, DPN symptoms often lead to sleep disorders, anxiety, and depression [ 20 , 21 ]. The poor glycemic control causing hyperglycemia and microangiopathy is the common underlying pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…According to Melzack's theory, psychological factors might affect pain severity perception, and pain could exist despite typical clinical examination results [15,16]. Kioskli et al in a systematic review, indicated that depression, anxiety, poor sleep, and low quality of life are consequences of PDN [17]. Various studies on chronic pain show that acceptance might improve pain management [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is worth highlighting that negative mood and anxiety are frequently observed processes in diabetic patients [15] and patients with neuropathic pain of different origins [16], and that the management and outcome of neuropathic pain in diabetic patients can worsen when these processes coexist with SD [2,17,18].…”
Section: Introductionmentioning
confidence: 99%